2011
DOI: 10.4161/cbt.12.10.17679
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of tissue factor suppresses hepatic metastasis and tumor growth in colorectal cancer via the downregulation of MMPs and the induction of autophagy and apoptosis

Abstract: Tissue factor (TF) is a significant risk factor for hepatic metastasis in patients with colorectal cancer (CRC). However, the mechanism by which TF promotes hepatic metastasis in CRC remains elusive. In this study, we first confirmed that TF expression was significantly correlated with lymph node metastasis, hepatic metastasis and TNM staging in clinical CRC samples, and found that TF expression in colon cancer cell lines was correlated with the invasion ability. Next, by employing TF-overexpressing LOVO cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…Intriguingly, hGAG significantly repressed the expression of TF in the B10F16 cells circulated in blood. Because TF expression in cancer cells has been shown to correlate with metastatic potential [52], [53] and the formation of pathological clots or thrombi in the veins of cancer patients [54], the reduction of TF expression might be a mechanism by which hGAG suppresses both metastasis and thrombosis in B16F10 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, hGAG significantly repressed the expression of TF in the B10F16 cells circulated in blood. Because TF expression in cancer cells has been shown to correlate with metastatic potential [52], [53] and the formation of pathological clots or thrombi in the veins of cancer patients [54], the reduction of TF expression might be a mechanism by which hGAG suppresses both metastasis and thrombosis in B16F10 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, TF‐targeted therapy is a promising strategy for treating cancer patients. Our recent study revealed that TF is a significant risk factor for the progression and hepatic metastasis in CRC patients 14. Indeed, specific inhibitor of the TF/fVIIa complex such as recombinant nematode anticoagulant protein c2 (rNAPc2) has been shown to exhibit a potent anti‐cancer effect when used in combination with chemotherapy or antiangiogenic therapy in several mice CRC models 24.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent studies demonstrated that TF contributes to the growth and hepatic metastasis of CRC in vitro and in vivo by the activation of anti‐apoptosis proteins and the induction of the expression of matrix metalloproteinases (MMPs). Moreover, lentivirus mediated knockdown of TF efficiently suppressed the migration and invasion of human colorectal adenocarcinoma LOVO cells in vitro, and hepatic metastasis of CRC in several nude mice models 14. In the present study, we aimed to investigate whether hyperthermia has synergistic effects with TF knockdown in inducing cytotoxicity on LOVO cells and suppressing CRC metastasis in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 97%
“…Polyglutamine (polyQ) aggregation in the ER induced autophagy via upregulation of ATG12 and probably via activation of the ATG5-ATG12-ATG16L1 complex, mediated by the PERK/eIF2α arm of the UPR [141]. The PERK-eIF2α-ATF4-CHOP arm induces autophagy in human hypoxic cancer cells [68] and in a tissue factor (TF) knockdown colon cancer cell line (LOVO cells) [142] via upregulation of both ATG5 and LC3. Radiation, a primary treatment modality for many aggressive tumors, can also induce autophagy in cancer cells, with either cytoprotective or lethal effects [143, 144].…”
Section: How the Upr Influences Tumor Cell Fate: Autophagy Senescmentioning
confidence: 99%
“…Although the PERK/eIF2α UPR arm confers cell survival and promotes metastasis by the induction of autophagy, the N-myc downstream regulated gene 1 (NDRG1) can act as a negative regulator on breast cancer cell lines, leading to apoptosis [193]. On the other hand, Tian et al , suggested that depletion of TF, which highly contributes to hepatic metastasis of colorectal cancer, promotes PERK/eIF2α/ATF4-dependent autophagy and apoptosis of LOVO cells, ultimately leading to inhibition of metastasis [142]. Similarly, suppression of the enzyme N-acetylglucosaminyltransferase V (GnT-V), which is overexpressed in a variety of human tumors and connected with tumor invasion and metastasis, causes the activation of both the PERK and IRE1/XBP-1 arms of UPR signaling, possibly leading to ER stress-dependent apop-tosis [194].…”
Section: The Role Of the Upr In Epithelial To Mesenchymal Transitimentioning
confidence: 99%